Family Business Succession: Appropriation Risk and Choice of Successor - Lee, Khai Sheang; Lim, Guan Hua; Lim, Wei Shi (Academy of Management Review, 2003)
Using a game theoretic approach and integrating research on managerial succession, family businesses, and transaction cost economics, we examine how the degree of idiosyncrasy of a family business and the ability of the family's offspring affect succession. Contrary to the popular belief that successors to family businesses are often offspring because of nepotism, we propose an economic rationale that this is due to the appropriation risk and the agency paradox that family businesses encounter in engaging agents.